Copper Extraction From Smelter Flue Dust By Lime Roast/Ammoniacal Heap Leaching - E. E. Caba (Society for Mining, Metallurgy & Exploration, 1992)
Copper smelter flue dusts containing arsenic are hazardous materials requiring environmentally accept-able disposal, preferably with re-source recovery under the RCRA and CRCLA regulations. However, the known resource recovery processes entail capital and operating costs greater than can be justified by the revenue of the recovered metal. Consequently, the smelting industry is tending to forego resource recovery in favor of encapsulation and storage in a certified class I hazardous waste site, or in a dedicated facility located at the source Superfund site. Order of magnitude costs for this option with portland cement encapsulation are estimated at $100 per ton, not including transportation. Industrial adoption of a new resource recovery process re-quires that its cost, including capital amortization, exceed the cost of encapsulation and storage only by the amount of the offsetting revenue from sale of metal. The lime-roast/ammoniacal leaching process is expected to meet this goal.